Respuesta :
Answer:
Step-by-step explanation:
9x⁴ – 2x² – 7 = 0
Let's say that u = x²:
9u² – 2u – 7 = 0
Factor:
(u – 1) (9u + 7) = 0
u = 1, -7/9
Since u = x²:
x² = 1, -7/9
x = ±1, ±i √(7/9)
By using the substitution method, the solutions of this equation (polynomial) is equal to C. x = ±1 and ±i√(7/9).
How to determine the solutions of an equation?
In order to determine the solutions of this equation (polynomial), we would let "u" be equal to x² and then substitute this value into the equation as follows:
9x⁴ - 2x² - 7 = 0
Substituting the value of "u" into the equation (polynomial), we have:
9u² - 2u - 7 = 0
Factorizing the equation (polynomial), we have:
(9u + 7)(u - 1) = 0
u = 1 and -7/9
Since, u = x²:
x² = 1 and -7/9
x = ±√(1 and -7/9)
x = ±1 and ±i√(7/9).
Read more on polynomials here: https://brainly.com/question/1600696
#SPJ5